2011
DOI: 10.1002/pssa.201026474
|View full text |Cite
|
Sign up to set email alerts
|

Structure characterization of spark plasma sintered alumina by positron annihilation lifetime spectroscopy

Abstract: Positron annihilation lifetime spectroscopy (PALS) measurements were performed to study the influence of the sintering temperature, heating rate and dwell time on the porosity and on the defect concentration on series of spark plasma sintered alumina samples. Two long‐lived components were found in the PALS spectra and were associated to pick‐off annihilation of ortho‐positronium localized in two types of pores. The same spectra were analysed in the frame of the three‐state‐trapping model and information for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The decrease in porosity with temperature illustrates that densification process during SPS is thermally activated. In our previous study by conventional positron annihilation lifetime spectroscopy (PALS) [18] we found that with the increase of the sintering temperature the size of the large intergranular pores increases while their concentration decreases in accordance with Figure 1 results. This effect was correlated to densification and grain growth processes.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The decrease in porosity with temperature illustrates that densification process during SPS is thermally activated. In our previous study by conventional positron annihilation lifetime spectroscopy (PALS) [18] we found that with the increase of the sintering temperature the size of the large intergranular pores increases while their concentration decreases in accordance with Figure 1 results. This effect was correlated to densification and grain growth processes.…”
Section: Resultssupporting
confidence: 85%
“…The approach is applicable only if a significant fraction of o-Ps which annihilates into 2 photons in the pores in the bulk of the sample. The PALS results revealed large intergranular pores [18]. This means that a great part of o-Ps confined in these pores annihilate by 3 photons.…”
Section: Resultsmentioning
confidence: 90%
“…The oxidation of UO 2 to UO 2. 27 facilitates clustering of open volume defects or Xe bubble formation as can be deduced from the higher S Ã d = 0.546 for OI compared to 0.532 for I. In the three cases I, OI and LI the depth position of the defect profiles is the same $40 nm (see Table 2) the only variation concerns the broadening of the distribution for OI.…”
Section: O/u Ratio and Grain Size Effectmentioning
confidence: 97%
“…The S/S bulk starts at relatively high value of $1.08 for low E and tends to 1 for high E. The value of 1.08 is a characteristic of the surface as a complex contribution of thermal positrons, surface positrons and positronium. An enhanced S/S bulk at low E is typical for materials in which positronium (Ps) is formed dominantly by surface electron capture [26] and Ps formation occurs also if voids exist in these materials [27][28][29]. Since the surface state is out of the scope of the study, this aspect will not be discussed further.…”
Section: Post-polishing Annealing and Xe Implantationmentioning
confidence: 97%
“…In fact, alumina was one of the most intensively analyzed materials in the framework of previously conducted SPS studies . Most publications in this area were dedicated to the analysis of mechanical or optical properties of spark plasma‐sintered alumina specimens. Some studies considered the impact of various process parameters on the alumina densification kinetics during SPS, and a limited number of works included modeling of the constitutive behavior or macroscopic modeling of the coupled phenomena occurring during SPS of alumina powder …”
Section: Introductionmentioning
confidence: 99%